ANALISIS PREFERENSI KONSUMEN TERHADAP PRODUK PAPA SULE (PUDING PANNA COTTA SUSU KEDELAI) DENGAN METODE IMPORTANCE-PERFORMANCE ANALYSIS - Khaznahar, Vitmaya; Larasati, Aisyah; Issutarti, Issutarti (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2018)
This article aims to analyze the consumer preferences on Papa Sule (Puding Panna Cotta Susu Kedelai) as a new product in order to optimize the product competitiveness with Importance-Performance Analysis. This research is qualitative-descriptive research that use enclosed questionnaire for data collected method. The results of the Importance-Performance Analysis shows that the main priority for improved performance is texture pudding in the mouth (number 2) and the completeness of the information on the label of packaging (number 10). The indicators that should be maintained because consumer consider it was important on the Papa Sule are product’s taste (number 1), the product is easily swallowed up (number 3), the level of robustness of the product (number 4), the overall scent which is not unpleasant (number 6), and the suitability of the packaging with the product size (number 8). Indicator of vanilla aroma on product (number 5) and packaging not dewy (number 9) can be improved performance but wasn’t the main priority. The last indicator which is the color of the product (number 7) can be ignored by its performance because consumer thought it less important for decisions in buying Papa Sule.